Recurrent Novel P2RY8/IGH Translocations in B-Lymphoblastic Leukemia/Lymphoma - Fang, Yanglan; Wang, Man; Hu, Shuhong; Wang, Tanzhen; Liu, Yujie; Xiao, Jinyan; Cai, Yiming; Wang, Ying; Qiu, Huiying; Tang, Xiaowen; Chen, Suning; Wu, Depei; et al. (Frontiers in Oncology, 2022)
Translocations involving the immunoglobulin heavy chain (IGH) locus are common abnormalities in B-cell acute lymphocytic leukemia (B-ALL), lymphoma, and multiple myeloma. These rearrangements result in a juxtaposition of IGH enhancers to the vicinity of oncogenes, such as MYC and CRLF2, leading to the upregulation of oncogenes. Here, we identified recurrent novel P2RY8/IGH translocations in three B-ALL patients by transcriptome sequencing. Exon 1 of P2RY8 was translocated to different sites of the IGH gene, resulting in P2RY8/IGHM, P2RY8/IGHV, and P2RY8/IGHD transcripts. Subsequently, a high expression level of P2RY8 was observed in the patients compared with healthy donors, which might be related to the aggressive clinical course and inferior outcome. In summary, we described recurrent novel P2RY8/IGH translocations with high expression levels of P2RY8, which may contribute to the guidelines for clinical diagnosis and treatment.